2016
DOI: 10.1007/s00011-016-0991-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen tension modulates the effects of TNFα in compressed chondrocytes

Abstract: Objective and designOxygen tension and biomechanical signals are factors that regulate inflammatory mechanisms in chondrocytes. We examined whether low oxygen tension influenced the cells response to TNFα and dynamic compression.Materials and methodsChondrocyte/agarose constructs were treated with varying concentrations of TNFα (0.1–100 ng/ml) and cultured at 5 and 21 % oxygen tension for 48 h. In separate experiments, constructs were subjected to dynamic compression (15 %) and treated with TNFα (10 ng/ml) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Our results are in accordance with a previous studies in which US exposure reduced the TNF-α plasmatic level in rabbit OA [41] and tissular TNF-α synthesis after muscle contusion [64]. In a study published by Tilwani, it was demonstrated that in chondrocytes' cultures biomechanical signals attenuated TNF-α-induced synthesis of NO, PGE 2 , and MMPs [22], molecules involved in chondrocytes and cartilage injury. Similarly, in our experimental model mechanical energy provided by US attenuated OS, TNF-α synthesis, so alleviating ultrastructural chondrocyte damages.…”
Section: Us Exposure Of Human Chondrocytes Cultures Prevented Ultrast...supporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in accordance with a previous studies in which US exposure reduced the TNF-α plasmatic level in rabbit OA [41] and tissular TNF-α synthesis after muscle contusion [64]. In a study published by Tilwani, it was demonstrated that in chondrocytes' cultures biomechanical signals attenuated TNF-α-induced synthesis of NO, PGE 2 , and MMPs [22], molecules involved in chondrocytes and cartilage injury. Similarly, in our experimental model mechanical energy provided by US attenuated OS, TNF-α synthesis, so alleviating ultrastructural chondrocyte damages.…”
Section: Us Exposure Of Human Chondrocytes Cultures Prevented Ultrast...supporting
confidence: 93%
“…TNF-α can also induce nitric oxide (NO), prostaglandin E 2 (PGE 2 ), and IL-6 synthesis and activate c-Jun N-terminal kinases (JNKs), which are responsible for upregulating proapoptotic genes and inactivating antiapoptotic proteins Bcl-2/Bcl-xL in OA chondrocytes [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, active mechanotransduction induces changes in oxygen tension and subsequent positive effects on matrix synthesis and cell growth (Urban, 1994; Park et al, 2004). These effects are explained by the displacement of growth factors or cellular cytokines by shifting cellular metabolism (Tilwani et al, 2017). Finally, our results showed that the proposed training offered an inflammatory control, confirmed by the modulation effect in biomarkers levels (IL1β and TNF in the joint wash; IL10 and IL6 in the knee joint).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated chondrocytes were subjected to equibiaxial cyclic tensile strain (CTS) at 0.33 Hz, 0–10% strain using the Flexcell FX-5000T™ system (Flexcell Corp, PA). Cartilage explants were subjected to cyclic compressive strain (CCS) at 0.33 Hz, 0–10% peak strain using a well-established Bose loading system as previously described 16 . Explants were mounted in a standard 24 well plate with each explant centrally located within a washer.…”
Section: Methodsmentioning
confidence: 99%